pH-responsive self-healing microcapsules, and preparation method and application thereof

CN122912758APending Publication Date: 2026-10-16SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611129705.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

传统解决方案,如采用贵金属合金或硬质陶瓷涂层,虽有一定耐蚀性,但存在成本高昂或脆性大、难以适应部件微动与热变形的问题;有机/无机复合涂层提供了良好的韧性与密封性,但其一旦因疲劳或腐蚀产生微裂纹,腐蚀介质将沿裂纹迅速渗透至基体,导致密封失效,且该过程不可逆

Benefits of technology

针对含氟聚合物工业中动态密封部件面临的高温和HF腐蚀工况,本发明提供了一种“被动阻隔+主动修复”的抗HF腐蚀的复合涂层,能够耐高温且有效防止腐蚀,延长涂层的使用寿命,并提高涂层在恶劣环境下的性能表现。其中,pH响应型自修复微胶囊起到“主动修复”的效果,当HF分子穿透涂层屏障或涂层产生微裂纹时,腐蚀区域的局部pH值迅速下降至4.0以下,囊壁中的缩醛键在H+催化发生水解断裂,囊壁交联密度迅速降至阈值以下,囊芯中全氟辛基三乙氧基硅烷和二月桂酸二丁基锡被全部释放至裂纹中,全氟辛基三乙氧基硅烷释放后铺展成膜,在催化剂二月桂酸二丁基锡和H+催化下水解缩合形成Si-O-Si交联网络,进而实现裂纹的密封。抗HF腐蚀的复合涂层还包括有机硅改性环氧树脂和纳米片状增强相,这两者起到“被动阻隔”的效果;有机硅改性环氧树脂固化后形成高度交联的三维网络结构,其Si-O-Si主链具有极低的自由体积分数和优异的气体阻隔性。同时,均匀分散的纳米片状增强相在涂层内部形成迷宫效应-纳米片层层堆叠,显著延长了HF气体分子的渗透路径,大幅降低了涂层的渗透系数。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912758A_ABST
    Figure CN122912758A_ABST
Patent Text Reader

Abstract

The present application relates to the surface protection technology field of mechanical parts under extreme working conditions, and particularly relates to a pH-responsive self-repairing microcapsule and a preparation method and application thereof. In view of the high-temperature and HF corrosion working conditions faced by dynamic sealing parts in the fluorine-containing polymer industry, the present application provides a composite coating with "passive barrier + active repair" anti-HF corrosion function, which can resist high temperature and effectively prevent corrosion, prolong the service life of the coating, and improve the performance of the coating in harsh environments. Among them, the pH-responsive self-repairing microcapsule plays an "active repair" effect, and the organic silicon modified epoxy resin and the nano-sheet-shaped reinforcing phase play a "passive barrier" effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface protection technology for mechanical parts under extreme working conditions, specifically to a pH-responsive self-healing microcapsule, its preparation method, and its application. Background Technology

[0002] In the processing industry of fluoropolymers (such as PTFE), the core dynamic sealing components of equipment (such as mechanical seals of melt pumps and high-temperature valves) are exposed to high temperatures, high pressures, and corrosive atmospheres of HF generated by polymer decomposition for extended periods. Traditional solutions, such as using precious metal alloys or hard ceramic coatings, offer some corrosion resistance, but suffer from high costs or brittleness, and are difficult to adapt to component fretting and thermal deformation. Organic / inorganic composite coatings provide good toughness and sealing performance, but once microcracks develop due to fatigue or corrosion, the corrosive medium will rapidly penetrate along the cracks to the substrate, leading to seal failure, and this process is irreversible.

[0003] To overcome these limitations, the concept of self-repair has been introduced into the coating material design process. When the coating material is damaged, it can achieve an active repair effect. Therefore, coating material design needs to simultaneously consider both ion barrier properties and self-healing capabilities to develop highly efficient anti-corrosion coatings with both passive barrier and active self-healing functions. Summary of the Invention

[0004] To overcome the above problems, the present invention provides a pH-responsive self-healing microcapsule, its preparation method and application.

[0005] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a pH-responsive self-healing microcapsule comprising a core and a capsule wall encapsulating the core; The core of the capsule comprises perfluorooctyltriethoxysilane and dibutyltin dilaurate; The capsule wall is formed by the condensation polymerization of hexamethylene diisocyanate with diol compounds containing acetal bonds and diethylenetriamine to form a pH-responsive polyurea-polyurethane.

[0006] In one or more embodiments, the molar ratio of the acetal-containing diol compound to hexamethylene diisocyanate is (0.4~0.6):1, preferably 0.5:1. The acetal-containing diol compound serves as the acid-sensitive structure. Limiting the molar ratio of the acetal-containing diol compound to hexamethylene diisocyanate limits the proportion of the acid-sensitive structure, thereby ensuring complete collapse and dissolution of the capsule wall under defined conditions, thus achieving a pH-responsive release capsule core.

[0007] In one or more embodiments, the diol compound containing an acetal bond is formed by the condensation polymerization of p-methoxybenzaldehyde and pentaerythritol; its structural formula is: .

[0008] A second aspect of the present invention provides a method for preparing the pH-responsive self-healing microcapsules described in the first aspect, comprising the following steps: Perfluorooctyltriethoxysilane, dibutyltin dilaurate and hexamethylene diisocyanate were mixed evenly to form the oil phase; A diol compound containing an acetal bond and diethylenetriamine are dispersed in an aqueous solution of polyvinyl alcohol (PVA), mixed evenly to obtain an aqueous phase, and the pH of the aqueous phase is adjusted to 9-10. The oil phase was added to the aqueous phase and subjected to high-speed shear emulsification to obtain an emulsion; then a low-speed stirring reaction was carried out, and the oil-water interface condensed to form pH-responsive self-healing microcapsules.

[0009] In one or more embodiments, the mass ratio of dibutyltin dilaurate to perfluorooctyltriethoxysilane is (0.5~1.8):10, preferably 1:10.

[0010] In one or more embodiments, the mass ratio of perfluorooctyltriethoxysilane to hexamethylene diisocyanate is 10:(2~3), preferably 4:1.

[0011] In one or more embodiments, the mass fraction of polyvinyl alcohol in the aqueous phase is 1.8-2.2%, preferably 2%. Diol compounds containing acetal bonds have limited solubility in the aqueous phase, but sufficient solubility and dispersion can be obtained in aqueous polyvinyl alcohol (PVA) solutions through the solubilizing effect of PVA.

[0012] In one or more embodiments, the molar ratio of hexamethylene diisocyanate to an acetal-containing diol compound and diethylenetriamine is 1:(0.4~0.6):(0.28~0.35).

[0013] In one or more embodiments, the concentration of the diol compound containing the acetal bond in the aqueous phase is 30-45 mmol / L.

[0014] In one or more embodiments, during high-speed shear emulsification, the shear rate is 1800~2200 rpm and the emulsification time is 4~6 min.

[0015] In one or more embodiments, during the low-speed stirring reaction, the stirring rate is 450~600 rpm and the reaction time is 1~3 h.

[0016] A third aspect of the present invention provides a composite coating resistant to HF corrosion, which uses an organosilicon-modified epoxy resin as a matrix and is loaded with pH-responsive self-healing microcapsules as described in the first aspect or pH-responsive self-healing microcapsules prepared by the preparation method described in the second aspect and a nanosheet-like reinforcing phase.

[0017] In one or more embodiments, the thickness of the HF corrosion resistant composite coating is 90~120 μm.

[0018] In one or more embodiments, the nanosheet-like reinforcing phase is hexagonal boron nitride (h-BN) or fluorinated graphene.

[0019] A fourth aspect of the present invention provides a method for preparing the HF corrosion-resistant composite coating described in the third aspect, comprising the following steps: After the silicone-modified epoxy resin prepolymer and curing agent are mixed evenly, pH-responsive self-healing microcapsules, nanosheet-like reinforcing phase and dispersant are added, and the mixture is mixed evenly again to obtain an anti-HF corrosion coating. Apply the HF corrosion resistant coating to the working surface of the dynamic sealing component and allow it to cure.

[0020] In one or more embodiments, the working surface of the dynamic sealing component needs to be pretreated before coating, including: After sandblasting and roughening, washing and drying, a silane coupling agent is sprayed on, and then dried.

[0021] Preferably, the silane coupling agent comprises γ-aminopropyltriethoxysilane (KH550).

[0022] In one or more embodiments, the mass ratio of silicone-modified epoxy resin prepolymer to curing agent is 10:3.

[0023] In one or more embodiments, the mass ratio of the silicone-modified epoxy resin prepolymer to the pH-responsive self-healing microcapsules, the nanosheet-like reinforcing phase, and the dispersant is 10:(2~3):1:0.1.

[0024] In one or more embodiments, the dispersant includes BYK-163 dispersant.

[0025] In one or more embodiments, the curing method includes: first leveling at room temperature for 20 to 40 minutes, then keeping at 75 to 85°C for 1.5 to 3 hours, and then raising the temperature to 140 to 160°C and keeping at 140 to 160°C for 2.5 to 4 hours.

[0026] In one or more embodiments, the thickness of the HF corrosion resistant composite coating is 90~120 μm.

[0027] In one or more embodiments, the dynamic sealing components include the dynamic and stationary rings of a mechanical seal, the valve core and valve seat of a control valve, the shaft sleeve and impeller port ring of a pump, the shaft seal ring of a stirrer, the compensation ring of a mechanical seal for a reactor, and a spring energy storage seal ring, etc.

[0028] The beneficial effects of this invention are as follows: To address the high-temperature and HF corrosion conditions faced by dynamic sealing components in the fluoropolymer industry, this invention provides a composite coating for resisting HF corrosion through a combination of passive barrier and active repair. This coating is capable of withstanding high temperatures and effectively preventing corrosion, extending the coating's service life and improving its performance in harsh environments. Specifically, pH-responsive self-healing microcapsules provide the "active repair" effect. When HF molecules penetrate the coating barrier or microcracks appear in the coating, the local pH value in the corroded area rapidly drops below 4.0. The acetal bonds in the capsule wall then react with the HF molecules in the H+ ions. + Catalytic hydrolysis and breakage occur, and the cross-linking density of the capsule wall rapidly decreases below the threshold. Perfluorooctyltriethoxysilane and dibutyltin dilaurate in the capsule core are completely released into the cracks. After release, the perfluorooctyltriethoxysilane spreads and forms a film, which then reacts with the catalyst dibutyltin dilaurate and H... + Catalytic hydrolysis and condensation form a Si-O-Si cross-linked network, thereby sealing the crack. The HF corrosion-resistant composite coating also includes silicone-modified epoxy resin and nanosheet-like reinforcing phase, which together act as a "passive barrier." After curing, the silicone-modified epoxy resin forms a highly cross-linked three-dimensional network structure, with its Si-O-Si backbone exhibiting extremely low free volume fraction and excellent gas barrier properties. Simultaneously, the uniformly dispersed nanosheet-like reinforcing phase creates a labyrinth effect within the coating—layers of nanosheets stacked—significantly extending the penetration path of HF gas molecules and greatly reducing the coating's permeability coefficient. Attached Figure Description

[0029] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0030] Figure 1 FTIR spectrum of pH-responsive self-healing microcapsules; Figure 2 The figure shows the pH response performance of the pH-responsive self-healing microcapsules. The inset shows the 24-hour release rate of the pH-responsive self-healing microcapsules at pH values ​​of 5.0, 6.0, 7.0, and 8.0. Figure 3 The graph shows the relationship between the proportion of acetal-diol-derived reaction bonds to the total cross-linked reaction bonds formed by -NCO groups and the response collapse time of pH-responsive self-healing microcapsules. Detailed Implementation

[0031] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0032] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0033] In response to the high temperature and HF corrosion conditions faced by dynamic sealing components in the fluoropolymer industry, this invention provides a composite coating for resisting HF corrosion that combines passive barrier and active repair. This coating can withstand high temperatures, effectively prevent corrosion, extend the service life of the coating, and improve the performance of the coating in harsh environments.

[0034] Among them, pH-responsive self-repairing microcapsules have an "active repair" effect: pH-responsive self-healing microcapsules include a core and a capsule wall encapsulating the core; wherein the core comprises perfluorooctyltriethoxysilane and dibutyltin dilaurate; the capsule wall is formed by the condensation polymerization of hexamethylene diisocyanate with diol compounds containing acetal bonds and diethylenetriamine to form pH-responsive polyurea-polyurethane.

[0035] When HF molecules penetrate the coating barrier or microcracks appear in the coating, the local pH value of the corroded area rapidly drops below 4.0, and the acetal bonds in the capsule wall are affected by the H+. + Under catalysis, hydrolysis and fracture occur, and the crosslinking density of the capsule wall rapidly decreases below the threshold. Perfluorooctyltriethoxysilane and dibutyltin dilaurate in the capsule core are completely released into the cracks. After release, the perfluorooctyltriethoxysilane spreads and forms a film. Under the catalyst dibutyltin dilaurate and H... + Catalytic hydrolysis and condensation form a Si-O-Si cross-linked network, thereby sealing the crack.

[0036] The pH-responsive self-healing microcapsules are triggered when the pH value drops below 4.0 and liquid water is present in the environment.

[0037] Regarding pH decrease: Fluoropolymers (such as polytetrafluoroethylene) undergo minor thermal decomposition at high temperatures (>250℃), releasing HF gas, which can reach concentrations of 100~5000 ppm in the microenvironment of the sealing surface. HF gas dissolves in the water molecule layer adsorbed on the metal surface to form hydrofluoric acid. The pH values ​​for different HF concentrations are calculated as follows: 100 ppm HF corresponds to approximately pH 3.5, 500 ppm to approximately pH 2.8, and 2000 ppm to approximately pH 2.2. More importantly, the crack tip is a semi-enclosed microspace where HF gas accumulates and concentrates. Combined with metal corrosion, this consumes F- and leaves H+, causing the local pH value inside the crack to be 1-2 units lower than the external environment. Therefore, as long as a microcrack (>0.1 μm) wide enough to accommodate HF diffusion appears on the sealing surface, the local pH value at the crack tip will rapidly drop below 3.0, far exceeding the trigger threshold (pH ≤ 4.0).

[0038] Regarding the existence of liquid water: According to the Kelvin equation: ln(p / p0) = -2γV m / (rRT), where r is the radius of curvature of the liquid surface. In cracks only 0.1-1 μm wide, the effective saturated vapor pressure of water decreases significantly. When r < 10 nm, capillary condensation can occur even in an atmosphere with a relative humidity of only 5%, forming a layer of liquid water molecules. Furthermore, the thermal decomposition of PTFE itself generates trace amounts of water vapor (polymer end-group oxidation), and the sealing surface experiences temperature cycling during equipment start-up and shutdown, producing condensate. The hydroxyl groups (-OH) on the metal surface have a natural adsorption effect on water molecules. These multiple water sources ensure that the microcracks always contain liquid water sufficient for the hydrolysis of perfluorooctyltriethoxysilane.

[0039] The long-term storage stability of pH-responsive self-healing microcapsules in areas undamaged by the coating before service is a prerequisite for achieving the long-lasting self-healing function of the coating. pH-responsive self-healing microcapsules provide systematic protection from the following levels: Complete separation of capsule wall preparation conditions and triggering conditions: The capsule wall is formed through interfacial condensation under alkaline conditions (pH 9-10), with acetal bonds accounting for 40%-60% of the capsule wall. It is completely stable under alkaline preparation conditions (acetal hydrolysis requires H+). + Catalysis, OH - (Does not catalyze acetal hydrolysis). Furthermore, the dense cross-linked network of the capsule wall provides effective isolation of perfluorooctyltriethoxysilane water under dry, neutral storage conditions.

[0040] Chemical inertness of the core: The Si-OEt bond of perfluorooctyltriethoxysilane hydrolyzes at an extremely low rate under alkaline conditions. Furthermore, the long perfluorinated chain of perfluorooctyltriethoxysilane endows it with extremely strong hydrophobicity, further repelling water molecules from penetrating into the oil droplet.

[0041] The mechanism of action of the catalyst is limited: the dibutyltin dilaurate added to the core acts as a condensation reaction catalyst, and its catalytic effect is specifically for the dehydration condensation reaction between silanol groups (-Si-OH); in the absence of water molecules and before the formation of silanol groups, the dibutyltin dilaurate is in an inert catalytic state and will not trigger any side reactions.

[0042] The HF corrosion-resistant composite coating also includes silicone-modified epoxy resin and nanosheet-like reinforcing phase, both of which act as a "passive barrier." After curing, the silicone-modified epoxy resin forms a highly cross-linked three-dimensional network structure with an extremely low free volume fraction and excellent gas barrier properties in its Si-O-Si backbone. Simultaneously, the uniformly dispersed nanosheet-like reinforcing phase creates a labyrinth effect within the coating—layers of nanosheets stacked—significantly extending the penetration path of HF gas molecules and greatly reducing the coating's permeability coefficient. Furthermore, the coupling agent between the coating and the metal substrate enhances the interfacial bonding through chemical bonding (Si-O-Me covalent bonds), effectively suppressing the lateral diffusion of corrosive media along the interface.

[0043] Furthermore, the perfluorooctyltriethoxysilane molecule contains a large number of stable CF bonds. Upon release, the fluorosilanol formed by partial hydrolysis on the metal surface can chemically bond with the hydroxyl groups (-OH) on the metal surface, forming a self-assembled hydrophobic monomolecular protective layer. This protective layer has extremely low surface energy, which not only endows the coating with excellent hydrophobic and oleophobic properties, but also provides additional passive protection in low-corrosion areas not triggered by microcapsules.

[0044] In the processing industry of fluoropolymers (such as PTFE), the core dynamic sealing components of equipment (such as mechanical seals of melt pumps and high-temperature valves) need to be resistant to HF corrosion and also to high temperatures. The high-temperature resistance mechanism of the composite coating for HF corrosion resistance provided by this invention is as follows: Thermal stability of the polymer matrix: The main chain of the organosilicon-modified epoxy resin has a Si-O-Si structure. The bond energy of the Si-O bond is much higher than that of the C-C and CO bonds in ordinary organic polymers, giving it excellent thermal stability. The thermal decomposition temperature (Td5%, air atmosphere) can reach over 350℃. Meanwhile, the introduction of aromatic ring groups such as phenyl groups further improves the rigidity and heat resistance of the resin. The strong electron-withdrawing effect of the CF bonds and trifluoropropyl side groups in the fluorosilicone rubber matrix allows it to maintain good elastic modulus and dimensional stability even at high temperatures of 300℃.

[0045] Thermal enhancement effect of nanosheet-reinforced phase: Hexagonal boron nitride (h-BN) has a graphite-like layered crystal structure, is stable at temperatures above 1000℃ in an inert atmosphere, and exhibits excellent oxidation resistance in air (operating temperature >850℃). The high thermal conductivity of h-BN nanosheets can rapidly conduct and disperse localized heat on the coating surface, avoiding hot spot formation and thermal stress concentration. Simultaneously, the extremely low coefficient of thermal expansion of h-BN nanosheets can form a gradient transition with the metal substrate, effectively alleviating thermal mismatch stress at the coating-substrate interface.

[0046] Heat resistance of the repair product: The fluorosiloxane cross-linked network formed by the curing of perfluorooctyltriethoxysilane released from the pH-responsive self-healing microcapsules exhibits thermal stability similar to PTFE. It does not degrade or depolymerize in an HF atmosphere or at temperatures above 250°C, ensuring the long-term durability of the repaired area. Based on the above mechanisms, the HF-resistant composite coating provided by this invention can achieve long-term stable protection for >2000 hours in an HF-containing atmosphere at 150°C~300°C.

[0047] To prevent coating peeling or delamination, this invention uses a silane coupling agent to treat the working surface of the dynamic sealing component. The Si-O-Me chemical covalent bond formed between the silane coupling agent and the metal substrate has a bond energy >200 kJ / mol, which is much higher than the physical adsorption force. It can still maintain a high bonding strength at the interface at high temperatures, effectively preventing the coating from peeling and delaminating during thermal cycling.

[0048] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0049] Example 1 Preparation of pH-responsive self-healing microcapsules: Mix 10 g of perfluorooctyltriethoxysilane, 2.5 g of hexamethylene diisocyanate and 1 g of dibutyltin dilaurate, and stir until homogeneous to obtain the oil phase.

[0050] 4 g of polyvinyl alcohol (PVA-1788, degree of alcoholysis 88%) was dispersed in 150 mL of deionized water. The system was heated to 90 °C and stirred to dissolve, then cooled to room temperature to obtain an aqueous solution of polyvinyl alcohol. Subsequently, 1.9 g of a diol compound containing acetal bonds, which is formed by the condensation of p-methoxybenzaldehyde and pentaerythritol, and 0.5 g of diethylenetriamine were added and mixed evenly. The pH was adjusted to 9.5 with 0.1 M NaOH aqueous solution, and water was added to make up to 200 mL to obtain an aqueous phase.

[0051] The oil phase was slowly added to the aqueous phase, and emulsified under high-speed shear (2000 rpm) for 5 min to form an O / W emulsion. The average droplet diameter of the perfluorooctyltriethoxysilane / hexamethylene diisocyanate mixture was approximately 20 μm. Subsequently, the stirring speed was reduced to 500 rpm, and the reaction was carried out in an ice bath at a controlled temperature (5-10°C) for 1 h. At the oil-water interface, the -NCO group in hexamethylene diisocyanate simultaneously condensed with the -OH group in acetal-containing diol compounds (forming urethane bonds) and the -NH2 group in diethylenetriamine (forming urea bonds). The acetal bonds were covalently embedded in the capsule wall crosslinking network, accounting for approximately 50% of the crosslinking points.

[0052] The product was filtered (using qualitative filter paper with a pore size of 5-10 μm), washed three times with deionized water, and vacuum dried at room temperature for 24 h to obtain white powdery microcapsules with an average particle size of about 20 μm, namely pH-responsive self-healing microcapsules.

[0053] Regarding the proportion of acetal bonds: The concentration of hexamethylene diisocyanate was 14.86 mmol, and the total amount of -NCO was 29.72 mmol. The diol compound containing acetal bonds formed by the condensation polymerization of p-methoxybenzaldehyde and pentaerythritol was 7.47 mmol, with a total of 14.94 mmol of -OH groups and a total of 7.47 mmol of acetal bonds. The diethylenetriamine content was 4.85 mmol, and the total -NH2 content was 14.55 mmol. The rate constant for the reaction between -NH2 and -NCO in diethylenetriamine is approximately 10. 3 ~10 4 The rate constant for the reaction of -OH with -NCO in diols containing acetal bonds is approximately 10 L / mol·s. -2 -10 -1 L / mol·s. Therefore, -NH2 preferentially consumes NCO.

[0054] The -NH2 in diethylenetriamine is 14.55 mmol, consuming an equal amount of NCO. The remaining -NCO = 29.72 - 14.55 = 15.17 mmol; The remaining -NCO 15.17 mmol reacted with the -OH group of the acetal diol. The acetal diol consumed was 15.17 / 2 = 7.59 mmol, and the diol compound containing the acetal bond was 7.47 mmol. The conversion rate was 98.4%, which is close to a quantitative reaction.

[0055] Based on the number of reacting bonds, each -NCO group forms one carbamate or urea bond. Therefore, the theoretical total number of reacting bonds, calculated based on the total -NCO group, is 29.72 mmol, and is not divided by 2. The percentage of reacting bonds originating from acetal diols = the amount of -OH reactions provided by acetal diols = 14.94 mmol. The percentage of reacting bonds related to acid-sensitive structures = 14.94 / 29.72 = 50.3% ≈ 50%.

[0056] A mixture of diethylenetriamine (trifunctional), hexamethylene diisocyanate, and diols containing acetal bonds (difunctional) has a Flory-Stockmayer gel theoretical percolation threshold of approximately 15-20%. Acetal bonds account for 50% of the cross-linking points, far exceeding the percolation threshold. Upon triggering, 50% of the cross-linking points break, causing the capsule wall to completely collapse and dissolve.

[0057] At room temperature and pH 5.0, the hydrolysis half-life of acetal bonds is 5.5 min. At room temperature and pH 4.0, the hydrolysis half-life of acetal bonds is 33 s. At 250℃ and pH 4.0, the hydrolysis half-life of acetal bonds is much less than 1 s. With a 50% acetal bond content, only about 0.5 half-lives (<1 second) are needed to exceed the percolation threshold.

[0058] Figure 1 The FTIR spectrum of pH-responsive self-healing microcapsules, from Figure 1 It can be seen from this that at 1630 cm -1 The characteristic absorption peak of the urea bond (-NH-CO-NH-) appears at 1720 cm⁻¹. -1 The characteristic absorption peak of the urethane bond (-NH-COO-) appears at 1130 cm⁻¹. -1 and 1050 cm -1 The characteristic absorption peak of acetal COC appears at 2270 cm⁻¹. -1 The -NCO groups completely disappeared. Furthermore, the characteristic peak of acetal COC in the pH-responsive self-healing microcapsules was significantly weakened after pH 4.0 treatment, confirming that the simultaneous hydrolytic breakage of high-density acetal bonds is the chemical mechanism of wall material collapse.

[0059] In addition, SEM observation showed that the microcapsules were regularly spherical with smooth and dense surfaces.

[0060] Figure 2 The figure shows the pH response performance of the pH-responsive self-healing microcapsules. When pH ≤ 4.0, the capsule begins to collapse within tens of seconds, and the release rate of the capsule core exceeds 98% within 30 minutes. However, when pH ≥ 5.0, the release rate is less than 3% after 24 hours. This quantitatively demonstrates the clear trigger threshold (pH 4-5) for matching the pKa of acetal bond acid hydrolysis.

[0061] Figure 3The graph shows the relationship between the proportion of acetal-derived reaction bonds to the total cross-linked reaction bonds of -NCO groups and the response collapse time of pH-responsive self-healing microcapsules. Figure 3 As can be seen, when the proportion of acetal bonds in the crosslinking points is 40%-60%, the overall performance of the microcapsules is optimal: under pH=4.0 conditions, the capsule wall begins to collapse within tens of seconds and completely dissolves within minutes, with a core release rate exceeding 98%. When this proportion is about 30%, it is only near the upper boundary of the theoretical permeation threshold, and continuous load-bearing links may still remain after acid hydrolysis, resulting in delayed initial collapse, significantly prolonged complete collapse time, and the risk of incomplete collapse and insufficient core material release. At a ratio of 70%, the increase in acid-sensitive links can further shorten the response time, but the relative decrease in non-acid-sensitive urea segments leads to a decline in capsule wall mechanical strength and storage stability margin. At a ratio of 80%, the aforementioned instability trend intensifies, making microcracks or premature leakage more likely during emulsification shearing, drying curing, and thermal cycling. When the ratio reaches approximately 90%, the capsule wall network is primarily controlled by acid-sensitive links. Although the acid triggering speed is fastest, capsule integrity, thermal cycling resistance, and long-term sealing are weakest, posing a higher risk of premature rupture and core leakage during processing or storage. Therefore, 70%–90% primarily improves response speed and does not necessarily indicate a further improvement in overall performance. Figure 3 As shown, in summary, the proportion of acid-sensitive structure-related reaction bonds is significantly higher than the percolation threshold (approximately 20%~30%), which can cause the amount of acid-broken bonds to cross the network instability critical point, thus supporting the complete collapse of the capsule wall upon triggering. However, this judgment still needs to be further verified through tests on collapse time, mechanical strength, and storage leakage rate of samples with different acetal proportions.

[0062] pH-responsive self-healing microcapsules maintained their morphology and had a core leakage rate of less than 3% after being stored under sealed and dry conditions for 6 months.

[0063] Example 2 Preparation of composite coatings resistant to HF corrosion: Modified to: Base: 316 stainless steel mechanical seal moving ring, roughened by sandblasting (Sa ≈ 3 μm), ultrasonically cleaned with anhydrous ethanol for 10 min to remove surface oil and impurities, and dried with nitrogen.

[0064] γ-aminopropyltriethoxysilane (KH550) was dissolved in an ethanol-water mixture (ethanol to deionized water volume ratio 95:5), acetic acid was added dropwise to adjust the pH to 5, and the mixture was stirred and allowed to stand for pre-hydrolysis for 30 min to obtain a 2% KH550 ethanol solution.

[0065] A KH550 ethanol solution was sprayed onto the substrate surface, with a wet film thickness controlled at 20 μm. The film was allowed to stand at room temperature for 30 min to allow the solvent to evaporate slowly, followed by drying at 110°C for 30 min. During drying, the Si-OH groups of KH550 condensed with the hydroxyl groups on the metal surface to form Si-O-Me covalent bonds, while excess Si-OH groups self-condensed to form a Si-O-Si crosslinked network. After complete solvent evaporation, the resulting coupling layer dry film thickness was approximately 0.15 μm.

[0066] Take 100 g of silicone-modified epoxy resin prepolymer (component A), add 30 g of curing agent (component B), stir and mix, add 25 g of pH-responsive self-healing microcapsules, 10 g of hexagonal boron nitride nanosheets (sheet diameter 1~2 μm) and 1 g of dispersant (BYK-163) prepared in Example 1, stir at 2000 rpm for 30 min using a high-speed shear emulsifier, and then degas under vacuum to obtain an anti-HF corrosion coating.

[0067] The anti-HF corrosion coating was applied to the working surface of the dynamic sealing component. After leveling at room temperature for 30 minutes, it was placed in an oven at 80℃ for 2 hours and then heated to 150℃ for 3 hours to complete the programmed step curing. The coating thickness was approximately 100 μm.

[0068] Comparative Example 1 Compared to Example 1, the aqueous phase did not contain diol compounds containing acetal bonds formed by the condensation of p-methoxybenzaldehyde and pentaerythritol, and the other methods were the same as in Example 1.

[0069] The HF corrosion resistant composite coating was prepared using the same method as in Example 2.

[0070] Experimental Example 1 Performance testing: Intelligent responsiveness testing: A micro-scratch (approximately 50 μm wide) was artificially created on the surface of the composite coatings prepared in Example 2 and Comparative Example 1, respectively. Half of the coating was immersed in a dilute hydrochloric acid solution with pH=4 (simulating an acidic environment caused by HF), while the other half was exposed to air. Within tens of seconds of immersion in the acid, microcapsules in the scratched area were observed to begin collapsing and dissolving, releasing a transparent repairing substance (perfluorooctyltriethoxysilane) and filling the scratch. After 24 hours, the scratch in the acid-immersed portion of the HF-resistant composite coating in Example 2 was completely filled with a transparent curing substance (confirmed to be fluorosiloxane by Fourier transform infrared spectroscopy), while the scratch in the air-exposed portion showed no signs of repair. In Comparative Example 1, the coating (acetal content 0%) showed no repair of scratches under both environments.

[0071] When the dilute hydrochloric acid solution with pH=4 was replaced with pure water (pH=7), it was found that the composite coating resisting HF corrosion in Example 2 did not show significant repair within 24 hours.

[0072] Dynamic corrosion-wear test: Sealing ring samples coated with either the HF corrosion-resistant composite coating of Example 2 or the composite coating of Comparative Example 1 were mounted on a simulated test bench and operated at 250°C, a contact pressure of 2 MPa, and a rotation speed of 500 rpm, with intermittent introduction of nitrogen gas containing HF. Electrochemical impedance spectroscopy (EIS) was used to monitor the coating impedance every 24 hours. The results showed that the impedance value of the HF corrosion-resistant composite coating of Example 2 decreased initially but then significantly rebounded and remained stable in subsequent cycles due to self-healing. In contrast, the impedance value of the composite coating of Comparative Example 1 continued to decrease, and obvious corrosion pits appeared on the coating after 150 hours. The bare substrate was severely corroded after 50 hours under the same conditions.

[0073] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A pH-responsive self-healing microcapsule, characterized in that, Includes the core and the capsule wall that covers the core; The core of the capsule comprises perfluorooctyltriethoxysilane and dibutyltin dilaurate; The capsule wall is formed by the condensation polymerization of hexamethylene diisocyanate with diol compounds containing acetal bonds and diethylenetriamine to form a pH-responsive polyurea-polyurethane.

2. The pH-responsive self-healing microcapsule as described in claim 1, characterized in that, The molar ratio of the diol compound containing the acetal bond to hexamethylene diisocyanate is (0.4~0.6):1, preferably 0.5:1; Alternatively, diols containing acetal bonds are formed by the condensation polymerization of p-methoxybenzaldehyde and pentaerythritol; their structural formula is: 。 3. The method for preparing the pH-responsive self-healing microcapsules according to claim 1 or 2, characterized in that, Includes the following steps: Perfluorooctyltriethoxysilane, dibutyltin dilaurate and hexamethylene diisocyanate were mixed evenly to form the oil phase; A diol compound containing an acetal bond and diethylenetriamine are dispersed in an aqueous solution of polyvinyl alcohol (PVA), mixed evenly to obtain an aqueous phase, and the pH of the aqueous phase is adjusted to 9-10. The oil phase was added to the aqueous phase and subjected to high-speed shear emulsification to obtain an emulsion; then a low-speed stirring reaction was carried out, and the oil-water interface condensed to form pH-responsive self-healing microcapsules.

4. The preparation method according to claim 3, characterized in that, The mass ratio of dibutyltin dilaurate to perfluorooctyltriethoxysilane is (0.5~1.8):10, preferably 1:10; Alternatively, the mass ratio of perfluorooctyltriethoxysilane to hexamethylene diisocyanate is 10:(2~3), preferably 4:1; Alternatively, in the aqueous phase, the mass fraction of polyvinyl alcohol is 1.8~2.2%, preferably 2%; Alternatively, the molar ratio of hexamethylene diisocyanate to a diol compound containing an acetal bond and diethylenetriamine is 1:(0.4~0.6):(0.28~0.35). Alternatively, the concentration of diol compounds containing acetal bonds in the aqueous phase is 30–45 mmol / L.

5. The preparation method according to claim 3, characterized in that, During high-speed shear emulsification, the shear rate is 1800~2200 rpm and the emulsification time is 4~6 min; Alternatively, when stirring at a low speed, the stirring rate is 450~600 rpm and the reaction time is 1~3 h.

6. A composite coating resistant to HF corrosion, characterized in that, It uses organosilicon-modified epoxy resin as a matrix and is loaded with pH-responsive self-healing microcapsules as described in claim 1 or 2, or pH-responsive self-healing microcapsules prepared by the preparation method described in any one of claims 3 to 5, and a nanosheet-like reinforcing phase.

7. The method for preparing the HF corrosion-resistant composite coating according to claim 6, characterized in that, Includes the following steps: After the silicone-modified epoxy resin prepolymer and curing agent are mixed evenly, pH-responsive self-healing microcapsules, nanosheet-like reinforcing phase and dispersant are added, and the mixture is mixed evenly again to obtain an anti-HF corrosion coating. Apply the HF corrosion resistant coating to the working surface of the dynamic sealing component and allow it to cure.

8. The preparation method according to claim 7, characterized in that, The working surface of dynamic sealing components requires pretreatment before coating, including: After sandblasting and roughening, washing and drying, a silane coupling agent is sprayed on, and then dried. Preferably, the silane coupling agent comprises γ-aminopropyltriethoxysilane (KH550).

9. The preparation method according to claim 7, characterized in that, The mass ratio of silicone-modified epoxy resin prepolymer to curing agent is 10:3; Alternatively, the mass ratio of silicone-modified epoxy resin prepolymer to pH-responsive self-healing microcapsules, nanosheet-like reinforcing phase, and dispersant is 10:(2~3):1:0.1; Alternatively, the dispersant may include BYK-163 dispersant; Alternatively, the curing method includes: first leveling at room temperature for 20~40 min, then keeping at 75~85℃ for 1.5~3 h, followed by raising the temperature to 140~160℃ and keeping at 2.5~4 h.

10. The preparation method according to claim 7, characterized in that, The thickness of the composite coating resistant to HF corrosion is 90~120μm; Alternatively, dynamic sealing components include the dynamic and static rings of a mechanical seal, the valve core and seat of a control valve, the shaft sleeve and impeller port ring of a pump, the shaft seal ring of an agitator, the compensation ring of a reactor mechanical seal, and a spring-loaded energy storage seal ring.